2008 15th IEEE International Conference on Image Processing 2008
DOI: 10.1109/icip.2008.4711802
|View full text |Cite
|
Sign up to set email alerts
|

Reducing boundary artifacts in image deconvolution

Abstract: In image deconvolution, the boundary value problem, if not appropriately handled, often causes serious ringing artifacts in the restored results. This paper proposes a simple method to tackle this problem without any assumption on the noise level and the symmetry of the Point Spread Function (PSF). We establish new boundary conditions by smoothly expanding the input image to a large tile. It helps reducing the boundary discontinuities and accordingly makes all restoration filters based on Fast Fourier Transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[28][29][30] Most of these issues become less pronounced when using a confocal microscopy system, which is also quite simpler in its hardware compared to a STED microscope. 31 Using the presented deep learning-based approach, the diffraction induced resolution gap between a STED image and a confocal microscope image can be closed, achieving super-resolution microscopy using relatively simpler and more cost-effective imaging systems, also reducing photo-toxicity and photo-bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Most of these issues become less pronounced when using a confocal microscopy system, which is also quite simpler in its hardware compared to a STED microscope. 31 Using the presented deep learning-based approach, the diffraction induced resolution gap between a STED image and a confocal microscope image can be closed, achieving super-resolution microscopy using relatively simpler and more cost-effective imaging systems, also reducing photo-toxicity and photo-bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…The content of each tiled block is computed by solving a regularized least square problem which imposes smooth transitions within the block itself and with the neighboring blocks' boundaries as well. 23 Since solving the optimization problem can be computationally heavy when large images are being processed, we approximate the content of the tiled blocks by a simple linear interpolation between the given boundary values, followed by adaptively blurring incrementally toward the center of the tiled blocks to impose smoothness. We found that these simple preprocessing steps are sufficient to eliminate the boundary artifacts with a light computation load.…”
Section: Tackling the Boundary Artifactsmentioning
confidence: 99%
“…The main SSD errors of our results concentrate at the image boundaries, which can be attributed to the boundary value problem inhere in the deconvolution using the fast Fourier transform (FFT). These boundary artifacts can be significantly reduced by Donatelli et al [5], Calvetti et al [32] and Liu et al [33].…”
Section: Objective Experimentsmentioning
confidence: 99%